INSTALASI OFFSHORE DERICK FLARE STACK DENGAN METODE SEGMENTAL - Sulardi Sulardi; Agus Sugianto; Basyaruddin Basyaruddin; Mardewi Jamal; Ali Arifin (Universitas Lambung Mangkurat, 2022)
One of the problems in the construction work of the offshore derick flare stack is the difficulty of lifting and installing the steel structure derick flare installation due to the limited length of the boom crane arm. This study aims to provide an overview of working methods to overcome these difficulties. The working method of handling the problem is dividing structural components segmentally, lifting and installing structural segments with roller-based lifting aids and steel ropes. The results showed that the work method was proven to be able to overcome problems and prevent potential delays in completing work. The results of this study also recommend that this work method can be replicated to overcome problems in other work units that experience similar problems.